ANALISIS FAKTOR-FAKTOR YANG MENENTUKAN VARIASI KEMAMPUAN BAHASA ARAB DI SEKOLAH INDONESIA JEDDAH - Apriyanti Faidatul Firdaus; Ainun Syarifah; Afif Wahyudi (El-Tsaqafah : Jurnal Jurusan PBA, 2025)
This study aims to analyze the factors that influence the variation in Arabic language proficiency at Sekolah Indonesia Jeddah (SIJ). In the context of the students' social environment, challenges arise due to the duality of languages ??faced by students, where Indonesian is used as the language of instruction at school, while Arabic is the dominant language in the surrounding community. This causes significant variation in students' proficiency in formal Arabic (fushah). The research methods used include observation and interviews with students and teachers at SIJ. The results showed that grade XI students generally have lower Arabic language proficiency compared to grade XII students, which is influenced by their language preferences and social environment. Most students are more comfortable using English or Indonesian in everyday interactions, even though they live in an Arabic-speaking country. External factors also play an important role in the development of students' Arabic language skills. Social interactions outside the family environment, as well as early exposure to Arabic, have been shown to influence students' language skills. However, many Indonesian families in Saudi Arabia prefer to use Indonesian at home, which reduces students' opportunities to practice Arabic naturally. The national curriculum, which is more oriented towards Indonesian as the main language of instruction in learning, is also a factor that influences students' Arabic language skills. Arabic is taught as an additional subject, which has the potential to limit students' mastery of formal Arabic. This study is expected to provide insight into the development of more effective learning methods in improving students' Arabic language skills at SIJ.